4 1/6*1 3/5+1 2/3=
21:4-2 1/2=
3 3/4+2 1/10*3 8/9=
3 5/12-2 11/12:1 1/9=



Odpowiedź :

Odpowiedź:

4 i 1/6 * 1 i 3/5 + 1 i 2/3 = 25/6 * 8/5 + 1 i 2/3 = 40/6 = 6 i 4/6 = 6 i 2/3

21 : 4 - 2 i 1/2 = 21 * 1/4 - 2 i 1/2 = 21/4 - 2 i 1/2 = 5 i 1/4 - 2 i 1/2 = 5 i 1/4 - 2 i 2/4 = 4 i 5/4 - 2 i 2/4 = 2 i 3/4

3 i 3/4 + 2 i 1/10 * 3 i 8/9 = 3 i 3/4 + 21/10 * 35/9 = 3 i 3/4 + 35/6 = 3 i 3/4 + 5 i 5/6 = 3 i 9/12 + 5 i 10/12 = 8 i 19/12 = 9 i 7/12

3 i 5/12 - 2 i 11/12 : 1 i 1/9 = 3 i 5/12 - 35/12 * 9/10 = 3 i 5/12 - 21/8 = 3 i 5/12 - 2 i 5/8 = 3 i 10/24 - 2 i 15/24 = 2 i 34/24 - 2 i 15/24 = 19/24